2019
DOI: 10.1021/acsnano.9b05703
|View full text |Cite
|
Sign up to set email alerts
|

Spill-SOS: Self-Pumping Siphon-Capillary Oil Recovery

Abstract: Oil spills remain a worldwide challenge and need emergency “spill-SOS” actions when they occur. Conventional methods suffer from complex processes and high cost. Here, we demonstrate a solar-heating siphon-capillary oil skimmer (S-SOS) that harvests solar energy, gravitational potential energy, and solid surface energy to enable efficient oil spill recovery in a self-pumping manner. The S-SOS is assembled by an inverted U-shape porous architecture combining solar-heating, siphon, and capillary effects, and wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 44 publications
1
31
0
Order By: Relevance
“…As shown in Figure 4(g, h), the results demonstrated that the main components of raw metal felt are Fe, Cr and Ni elements, which is consistent with previously reported publications. 8 Extra Si and O elements were detected in the coated metal felt and exhibited an atomic ratio of ~1: 2, which confirmed the coating is composed of silicon dioxide. As shown in Figure S5, the FTIR spectroscopy reveals that plenty of hydroxyl appeared on the metal felt after being coated with SiO2 NPs.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…As shown in Figure 4(g, h), the results demonstrated that the main components of raw metal felt are Fe, Cr and Ni elements, which is consistent with previously reported publications. 8 Extra Si and O elements were detected in the coated metal felt and exhibited an atomic ratio of ~1: 2, which confirmed the coating is composed of silicon dioxide. As shown in Figure S5, the FTIR spectroscopy reveals that plenty of hydroxyl appeared on the metal felt after being coated with SiO2 NPs.…”
Section: Resultsmentioning
confidence: 82%
“…Conventional treatment techniques including gravity separation, centrifuge, air-flotation and biodegradation, have been employed to separate stratified oil/water mixtures. [7][8][9] Nevertheless, the emulsified droplets in an emulsion usually have a diameter less than 20 μm and are extremely stable due to the adsorption of surfactant at the oil/water interface. [10][11][12] They do not easily coalesce and cannot easily be separated by aforementioned traditional methods.…”
Section: Introductionmentioning
confidence: 99%
“…Reproduced with permission. [ 89 ] Copyright 2019, American Chemical Society; d) aborption sponge coupling solar heating and Joule heating. Reproduced with permission.…”
Section: Sustainable Applications Of Photothermal Materialsmentioning
confidence: 99%
“…[ 85 ] On the other hand, Wu et al developed a self‐pumping photothermal oil‐collection device based on the siphonic and capillary effects (Figure 2c). [ 89 ] An all‐carbon porous felt with hierarchical architecture was fabricated by growing vertically oriented graphene nanosheets on a monolith of graphite felt through plasma‐enhanced chemical vapor deposition. The oleophilic porous structure could absorb the oil through the capillary effect at the beginning and then transport the oil from one side to the other side under a height difference based on the siphon.…”
Section: Sustainable Applications Of Photothermal Materialsmentioning
confidence: 99%
See 1 more Smart Citation